The Effectiveness of Clopidogrel and Omeprazole in preventing recurrent of ischemic stroke among ischemic stroke patients at Nangrong Hospital, Narong District, Buriram Province - Banjong, Jakkrid (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2024)
Ischemic stroke is a common condition among elderly people that can lead to various health problems and even death. Preventing recurrent ischemic stroke is crucial for physicians to improve patient treatment and reduce mortality. This study aims to evaluate the effectiveness of Clopidogrel and Omeprazole in preventing recurrent ischemic strokes. An analytical retrospective case-control study was conducted on ischemic stroke patients who were given Clopidogrel to prevent recurrence. The study included residents of Nangrong aged 18 and older who were newly treated with Clopidogrel following an ischemic stroke between January 1, 2018, and December 31, 2022, at Nangrong Hospital in Buriram province. The case patients were those who were readmitted within a year following their initial diagnosis of ischemic stroke. Control patients were individuals who had remained stroke-free for at least one year and were matched with case patients in terms of age and gender at a 1:1 ratio. The results showed that among the 1,118 patients who received newly initiated Clopidogrel treatment for ischemic stroke, 139 cases were readmitted for the same condition within one year. We matched these cases with 139 controls and found that 116 patients (83.4%) in the case group and 126 patients (90.6%) in the control group were also treated with Omeprazole. After conducting multivariable analysis, we determined that the concurrent use of Omeprazole and Clopidogrel did not significantly increase the risk of recurrent ischemic stroke. The adjusted odds ratio was0.55 (95% CI = 0.25–1.22). Therefore, we can conclude that the simultaneous administration of Omeprazole and Clopidogrel is not associated with an elevated risk of recurrent ischemic stroke.